Physical Neglect has become the Most Common Category of Child Neglect in Sri Lanka - Serasinghe, H (International Journal of Research and Innovation in Social Science, 2021)
Neglecting the child could be a factor for generating mentally and physically ill people all around the world. Child neglect has simply defined the avoidance of primary care and failure to provide basic facilities including food, clothing, healthcare, education for the child by their parents or guardian. Child neglect considers as the most prevalent category of child abuse not only in Sri Lanka but also worldwide. Child welfare specialists form common categories of neglect including physical neglect, medical neglect, inadequate supervision, environmental neglect, emotional neglect, educational neglect. Though previous researchers have identified all the above categories of child neglect, there is no research have done to identify the most common category of child neglect in the Sri Lankan Context. The objective of this study is to identify the most common category of child neglect in Gampaha district, western province, Sri Lanka. Primary data were collected using mixed research method. Distributed structured questionnaires (N=134) and conducted semi-structured interviews (N=10) from neglected children who were reported in Gampaha District, Sri Lanka. The researcher used descriptive statistics, factor analysis, and content analysis for analyzing purposes. The findings show the physical neglect is the most common type of child neglect while the cognitive neglect type has the lowest respondents. Supervision and emotional neglect indicated third and fourth places respectively. Government should take necessary action in assigning relevant officers including Child Rights Promoting Officers, Social Workers, Gramasewaka, and active officers for the relevant committees in order to spot children who are neglected by their families
Keywords: Child abuse, Child Neglect, Child Neglect Categories, Commonest child neglect category